2015
DOI: 10.1371/journal.pone.0132413
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Genotoxic Study: Chromosome Damage Two and Six Years after Exposure to the Prestige Oil Spill

Abstract: BackgroundThe north-west coast of Spain was heavily contaminated by the Prestige oil spill, in 2002. Individuals who participated in the clean-up tasks showed increased chromosome damage two years after exposure. Long-term clinical implications of chromosome damage are still unknown.ObjectiveTo realize a follow-up genotoxic study to detect whether the chromosome damage persisted six years after exposure to the oil.DesignFollow-up study.SettingFishermen cooperatives in coastal villages.ParticipantsLocal fisherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…There was no improvement in the pulmonary function and biological respiratory parameters after four years of follow-up in the fishermen exposed to fuel, although there was no clear data indicating that the degree of exposure was associated with the long-term effects 14 . A long-term genotoxic study, conducted in 52 exposed and 23 non-exposed individuals, showed that structural alterations remained high in exposed individuals, although the association with the exposure to the oil spill could not be substantiated because there was a relevant increase of structural alterations in nonexposed individuals 15 . Nevertheless, 2p23 and 2q23 chromosome bands were only detected in exposed individuals 16 The main results of the SEPAR-Prestige Study are summarised in table 2.…”
Section: Major Findings Of the Separ-prestige Studymentioning
confidence: 99%
“…There was no improvement in the pulmonary function and biological respiratory parameters after four years of follow-up in the fishermen exposed to fuel, although there was no clear data indicating that the degree of exposure was associated with the long-term effects 14 . A long-term genotoxic study, conducted in 52 exposed and 23 non-exposed individuals, showed that structural alterations remained high in exposed individuals, although the association with the exposure to the oil spill could not be substantiated because there was a relevant increase of structural alterations in nonexposed individuals 15 . Nevertheless, 2p23 and 2q23 chromosome bands were only detected in exposed individuals 16 The main results of the SEPAR-Prestige Study are summarised in table 2.…”
Section: Major Findings Of the Separ-prestige Studymentioning
confidence: 99%
“…Moreover, due to certain volatile organic oil compounds, in particular benzene, being carcinogenic in humans [3], it is very important to determine if exposure to oil during clean-up tasks is associated with genotoxic effects in the short-(less than 12 months) and long-term (more than one year). So far, only a few human genotoxic studies in oil exposed populations have been published, most after the wreck of the Prestige [4][5][6][7][8][9][10][11][12][13][14]. In general, these studies revealed increased genomic damage in exposed individuals during the clean-up tasks [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies revealed increased genomic damage in exposed individuals during the clean-up tasks [4][5][6][7][8][9][10][11]. Nevertheless, only two research groups have carried out long-term genotoxic studies after oil exposure to the Prestige [12][13][14][15], with conflicting results. In one group, the authors described an increase of structural chromosome alterations in highly exposed vs. non-exposed individuals two and six years after exposure [12][13][14], this follow-up study reveal that chromosome damage persisted at least for the six years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations